Grammatical Errors in Using the Simple Present Tense in Writing Descriptive Texts - Martina Napratilora; Ahlis Sarah (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
Simple present tense was often used by students in writing and speaking, so they needed to know and understand how to use it correctly, especially in writing descriptive texts. In reality, students still make various mistakes in using the simple present tense, including errors in writing nominal sentences, such as incorrect subject-verb agreement, improper placement of "not" and "to be" in negative sentences, and incorrect word order in interrogative sentences. Additionally, students make errors in verbal sentences, such as using inappropriate verbs for the subject, incorrect spelling, misplacing the suffix "s" or "es" in verbs, and forgetting to add auxiliary verbs "do/does" in negative and interrogative sentences. Article misuse is also a common issue. The study purpose was to determine the dominant errors in using the simple present tense made by students in writing descriptive texts based on the surface strategy taxonomy. The method used in this study was a literature approach. The theory of literature research is taken from several sources such as textbooks, encyclopaedias, journals, papers, dissertations, and the internet related to errors in the use of simple present tense in writing descriptive texts. The criteria for journal articles used in this study are journals published in 2020-2024 with the keywords "errors, grammar, simple present tense, descriptive text". The results of the study showed that "omission" is the most dominant aspect of errors made by students in using simple present tense when writing descriptive texts and is followed by "misformation, addition, and misordering". This occurs due to several factors including students' lack of understanding of grammar rules in English, differences in the structure of the first and second languages, limited vocabulary, lack of focus, carelessness, lack of teacher guidance in learning activities, and the complexity of the simple present tense. Therefore, the dominant grammatical errors in using the simple present tense in writing descriptive texts were omission.